2020
DOI: 10.14202/vetworld.2020.508-514
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and cytotoxic activity assessment of Channa striatus (Haruan) extract

Abstract: Background and Aim: Channa striatus extract, a freshwater snakehead fish known as Haruan, is popular in Southeast Asia for consumption and as a traditional therapeutic remedy for wound healing. C. striatus is also used in osteoarthritic for its anti-inflammatory. The aim of this study was to determine the presence of antibacterial properties of C. striatus extract against oral bacteria and to investigate the cytotoxic activity against Vero cells. Materials and Methods: The authors prepared C. striatus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…To evaluate the general antimicrobial activity of A. pluriseta crude and solvent fractions extracts at various specified concentrations, we used the modified disc diffusion method [ 57 , 58 , 59 , 60 , 61 ]. A fresh microbial inoculum was made by suspending activated colonies in physiological saline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the general antimicrobial activity of A. pluriseta crude and solvent fractions extracts at various specified concentrations, we used the modified disc diffusion method [ 57 , 58 , 59 , 60 , 61 ]. A fresh microbial inoculum was made by suspending activated colonies in physiological saline.…”
Section: Methodsmentioning
confidence: 99%
“…The MIC and MMC of A. pluriseta solvent fractions were analyzed as previously described [ 36 , 57 , 60 , 61 , 63 ]. Briefly, 50 μL of varying fraction concentrations (3.9–500 μg/mL petroleum ether, dichloromethane, and methanol; 1.95–250 μg/mL ethyl acetate) were added into 100 μL of nutrient broth held in a sterile 96-well plate followed by addition of 50 μL test organisms adjusted to 0.5 McFarland standard.…”
Section: Methodsmentioning
confidence: 99%
“…The last column of microtiter well plate containing medium without plant solvent extract fractions, but with 1% DMSO, was included as the negative control. The percentage cell viability (%) was calculated at each concentration using the formula provided below [ 1 , 20 , 23 ]. …”
Section: Main Textmentioning
confidence: 99%
“…In recent years, extensive work has been conducted to analyse the antibacterial effects of the mucus of fish species [93][94][95][96][97], including the Channa species. Several research studies [48,[98][99][100][101][102][103][104] were performed over the years to evaluate the antibacterial and antifungal activities of Haruan. Most of the studies [99][100][101][102][103][104] revealed that Haruan displays some antimicrobial activities, except two studies [98,99] which detected negligible inhibitory effects against Staphylococcus aureus and Escherichia coli strains respectively.…”
Section: Antimicrobial Effectsmentioning
confidence: 99%